Reactive compatibilizers on mechanical and morphology properties of Poly(vinyl chloride) / Polyisopere blends - Supri, A. Ghani; Salmah, Husseinsyah; Che Mohd Ruzaidi, Ghazali (Universiti Malaysia Perlis, 2010)
In this works, an experimental was performed do determine the influence of reactive compatibilizers of poly (vinyl chloride) / polyisoprene blends. The effect of methyl methacrylate and acrylic acid contents on mechanical properties and tensile fracture surfaces of poly(vinyl chloride) / polyisoprene blends were investigated. Scanning electron microscopy study shows that the methylmethacrylate more compatible with poly (vinyl chloride)-polyisoprene than acrylic acid. The experimental results show that there is a strong correlation between mechanical properties and tensile fracture surfaces in the PVC / polyisoprene blends.